LCA in Process Development: Case Study of the OxFA-Process - Rauch, Simon; Piepenbreier, Frank; Voß, Dorothea; Albert, Jakob; Hartmann, Martin (Progress in Life Cycle Assessment, 2019)
In the context of environmental problems and resource depletion, the chemical industry is challenged with the substitution of fossil feedstock by renewable resources. To reduce the probability of unexpected environmental impacts by new processes using various sources of biomass, LCA methods can provide support for process development. The investigated OxFA-process, which converts biomass into formic acid, is a typical representative for these next generation processes. However, at an early development stage, data gaps have to be handled. In this study, scientific literature, process simulation and generic data have been used to identify the catalyst, compressed air and energy consumptions as those process components are the ones that significantly influence the environmental footprint of the whole process. Hereby starting points for an effective process optimization are shown and different scenarios for process implementation are compared. Furthermore, a first estimation of the competitiveness with the state-of-the-art process was attempted. Despite some data inaccuracies and required estimations, it is fair to assume that the OxFA-process is an ecological reasonable alternative.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Biomass; Formic acid; Life cycle assessment; OxFa process